Ride It or Miss Out: Unpacking Consumer Behavior Intentions for Whoosh High-Speed Rail - Wahpiyudin, Cep Abdul Baasith; Sumarwan, Ujang; Simanjuntak, Megawati; Nani, Irvan (Jurnal Aplikasi Manajemen, 2025)
Despite extensive global research on high-speed rail (HSR) adoption, studies often overlook the unique socio-economic and environmental challenges in emerging markets like Indonesia, including rapid urbanization, private vehicle reliance, and shifting attitudes toward sustainability. This paper aimed to help policymakers design strategies to accelerate HSR adoption and support Indonesia's sustainability goals. Using a quantitative approach, this study examined factors influencing the behavioral intention to adopt high-speed rail (Whoosh) in Indonesia. Data were collected via purposive sampling, targeting respondents from Jakarta and Bandung with specific criteria, resulting in 367 valid responses. The questionnaire entailed demographic questions and items measuring constructs based on the Theory of Planned Behavior and related frameworks, using a five-point Likert scale. Data analysis incorporated descriptive statistics with SPSS and Structural Equation Modeling (SEM) with SmartPLS to validate measurement models and test hypotheses. The results indicate that subjective norms, perceived moral obligations, attitudes, perceived quality, and environmental impact significantly affect behavioral intention (BI), with attitudes being the strongest predictor. Trust influenced subjective norms but did not affect perceived moral obligations or attitudes. External influences, including government campaigns and media, shaped trust, subjective norms, and novelty-seeking behavior. Additionally, environmental impact influenced perceived sustainability, and novelty-seeking behavior positively impacted attitudes toward high-speed rail. These findings offer valuable insights into factors driving adoption and provide implications for policymakers and transportation planners.